(untitled) (Pedagogical Horizons, 2020)
This article introduces the initative „StiA – Studierende im Aufbruch” as a possibility to satisfy equally primary educational purpose of the University of Education (f.e. consideration of students needs and professional guiding of their autonomous activity) and students´ efforts for autonomy and the experience of competence. A brief introduction of the initative StiA is followed by the description of the research-related elements as the criterias of a) research-based learning (CILI), b) increasing competence, effort, motivation and personal relevance (IMI, SIMS) and c) curiosity (CEI-II). These descriptions are followed by an empirical study with the aim to prove if the initative StiA follows the demands mentioned above.